A Distinct Class of Antibodies May Be an Indicator of Gray Matter Autoimmunity in Early and Established Relapsing Remitting Multiple Sclerosis Patients. (19th October 2015) - Ligocki, Ann J.; Rivas, Jacqueline R.; Rounds, William H.; Guzman, Alyssa A.; Li, Min; Spadaro, Melania; Lahey, Lauren; Chen, Ding; Henson, Paul M.; Graves, Donna; Greenberg, Benjamin M.; Frohman, Elliot M.; et al.
* These authors contributed equally to the work in this manuscript. We have previously identified a distinct class of antibodies expressed by B cells in the cerebrospinal fluid (CSF) of early and established relapsing remitting multiple sclerosis (RRMS) patients that is not observed in healthy donors. These antibodies contain a unique pattern of mutations in six codons along VH 4 antibody genes that we termed the antibody gene signature (AGS). In fact, patients who have such B cells in their CSF are identified as either having RRMS or developing RRMS in the future. As mutations in antibody genes increase antibody affinity for particular antigens, the goal for this study was to investigate whether AGS + antibodies bind to brain tissue antigens. Single B cells were isolated from the CSF of 10 patients with early or established RRMS. We chose 32 of these B cells that expressed antibodies enriched for the AGS for further study. We generated monoclonal full-length recombinant human antibodies (rhAbs) and used both immunological assays and immunohistochemistry to investigate the capacity of these AGS + rhAbs to bind brain tissue antigens. AGS + rhAbs did not recognize myelin tracts in the corpus callosum. Instead, AGS + rhAbs recognized neuronal nuclei and/or astrocytes, which are prevalent in the cortical gray matter. This pattern was unique to the AGS + antibodies from early and established RRMS patients, as AGS + antibodies from an early neuromyelitis optica patient did not display the same reactivity. Prevalence of CSF-derived B cells expressing AGS + antibodies that bind to these cell types may be an indicator of gray matter-directed autoimmunity in early and established RRMS patients.